Bali Imagined in the Context of Tourism - Darma Putra, I Nyoman; Hitchcock, Michael (E-Journal of Tourism; Volume 8 Number 2 (September 2021), 2021)
The contention that Bali has been imagined in the context of tourism and that these images do not necessarily correspond to the realities of the destination is not entirely new. However, what this paper argues is that imaginings have occurred over time and began well before the advent of tourism, before becoming incorporated into a more fully developed and more globally recognised tourism image with many elements of the ‘tourist gaze’. These gazes are not just externally derived, but also owe a lot to local imaginings of what Bali might be, namely the notion that Bali is some kind of heir to the renowned Hindu-Javanese kingdom of Majapahit based in Java. This paper traces the evolution of these images blending earlier reports of seafarers, colonial administrators both Dutch and British, as well as artists who have lived on the island, into the world of the contemporary media-scape.